Association between platelet counts and morbidity and mortality after endovascular repair for type B aortic dissection. (2nd January 2022) - Xie, Enmin; Liu, Jitao; Liu, Yuanhui; Liu, Yuan; Xue, Ling; Fan, Ruixin; Xie, Nianjin; Ding, Huanyu; Hu, Binquan; Chen, Lyufan; Yang, Xinyue; Yang, Fan; et al.
Abstract: This study aimed to assess the association of postoperative platelet counts with early and late outcomes after thoracic endovascular aortic repair (TEVAR) for type B aortic dissection (TBAD). We retrospectively evaluated 892 patients with TBAD who underwent TEVAR from a prospectively maintained database. Postoperative nadir platelet counts were evaluated as a continuous variable, and a categorical variable (thrombocytopenia), which was defined as platelet count≤ the lowest 10% percentile (108 × 10 9 /l). Multivariable logistic regression analyses were conducted to assess the impact of postoperative thrombocytopenia on early outcomes, and multivariable cox regression analyses on long-term mortality. Patients with postoperative thrombocytopenia experienced significantly higher rates of postoperative mortality, prolonged intensive care unit stay, death, stroke, limb ischemia, mesenteric ischemia, acute kidney injury (AKI), and puncture-related hematoma ( P < .05 for each), but similar rates of immediate type I endoleak and spinal cord ischemia. Multivariable logistic analyses showed that postoperative thrombocytopenia was independently associated with postoperative stroke, limb ischemia, and AKI. Similar results were observed when postoperative nadir platelet count was modeled as a continuous predictor ( P < .05 for each). By multivariable Cox analyses, postoperative thrombocytopenia was an independent predictor for long-term all-cause mortality (hazard ratio 2.72, 95% CI, 1.72–4.29, P < .001). For every 30 × 10 9 /L decrease in postoperative platelet count, the risk of long-term all-cause mortality increased by 15% (HR 1.15; 95% CI 1.07–1.25; P < .001). Therefore, postoperative thrombocytopenia might be a useful tool for risk stratification after TEVAR.